Dermanyssus gallinae (Acari: Dermanyssidae) (DE GEER, 1778): colonização e resposta de protoninfas alimentadas a correntes de ar e a odores de extratos de ácaros co-específicos em olfatometro dixriminante - Lucas Maciel Cunha (2008)
Dermanyssus gallinae ingurgitated protonymphs were submited to laminar flow winds or rubber septa stopper (RSS) containing hexanic or dichloromethanic conspecific extracts in a discriminant olfactometer. The D. gallinae feeded protonymphs latency time (akinetic response)and the time for these mites to leave the test area in olfactometer was similar (p0,05) when D. gallinae feeded protonymphs were exposed to winds of zero cm/s, 10±2 cm/s, 20± 2 cm/s or 30±2 cm/s. Each individual D. gallinae feeded protonymphs route line was measured and the cosine averages (CA) were used to demonstrate the predominant positions of the mites. D. gallinae feeded protonymphs exposed to different wind velocities did not show statistic difference (p0,99) in these CAs. The mites CA exposed to odor plumes of RSS containing zero, 200 and 500 equivalent-mites per milliliter (eq/mL) dichloromethanic or hexanicconspecific extracts did not show statistic difference (p0,99). However the route line angules histogram of these mites exposed to 500 eq/mL dichloromethanic extracts shows an atratraction behavior. The proportion of mites that eather touched or reached 1 mm distance of RSS impregnated with zero, 200 and 500 eq/mL hexanic extracts did not show statistic difference (p0,01).The proportion of protonymphs that eather or touched or reached 1 mm distance of RSS impregnated with zero and 200 eq/mL; or 200 and 500 eq/mL dichloromethanic extracts did not show statistic difference (p0,05), but more protonymphs touched or reached 1 mm distance of rubber septa stopper impregnated with 500 eq/mL dichloromethanic extracts than zero eq/mL (control group) rubber septa (p0,01). These results show the absence of laminarwind anemotaxis and abcense of pheromone repellence of D. gallinae feeded protonymphs. However these mites show an atraction and an arrestment-like clumping caused by non volatile and non-unpollar pheromones